Boundary filtering approach in surface reconstruction. (10th July 2007) - Varnuska, Michal; Kolingerova, Ivana
One of the methods for 3D data model acquisition is real object digitisation followed by surface reconstruction. Many algorithms have been developed to do this, each with its advantages and disadvantages. We use for the reconstruction a CRUST algorithm by Nina Amenta, which selects surface triangles from the Delaunay tetrahedronisation using information from the dual Voronoi diagram. Unfortunately, these candidate surface triangles do not form a manifold, so it is necessary to perform some other steps for manifold extraction. In this paper, we present some observations and modifications for this step, which improve the quality of the resulting mesh especially in the case, when the surface contains boundaries.